Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Melalui Permainan Sepakbola Terhadap Kepercayaan Diri Dan Keterampilan Gerak Dasar Pada Siswa Sekolah Dasar - Khamdani, Muhammad Nauval (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aims to determine the effect of applying the Jigsaw cooperative learning model on self-confidence and basic football skills of fifth-grade students at SD Negeri 1 Suranenggala, Cirebon Regency. The research method used was a quasi-experimental design with a Pretest-Posttest Control Group Design. The sample consisted of 20 male students in the fifth grade, selected using a purposive sampling technique. The research instruments included the Game Performance Assessment Instrument (GPAI) to measure football playing skills and the Athlete Self-Confidence Questionnaire (ASQ) to assess students’ self-confidence. Data were analyzed using normality, homogeneity, and paired sample t-tests.The results showed a significant improvement in both self-confidence and basic football skills after the implementation of the Jigsaw model. The average pretest score of football skills was 2.38, which increased to 3.18 in the posttest. The paired t-test revealed a significance value of Sig. (2-tailed) = 0.000 < 0.05, indicating a significant difference between pretest and posttest results. In conclusion, the Jigsaw cooperative learning model has a positive and significant effect on enhancing students’ self-confidence and basic football skills in elementary school.